Prevalence and associated factors of stillbirth among women at extreme ages of reproductive life in Sub-Saharan Africa: a multilevel analysis of the recent demographic and health survey - Alebachew Ferede Zegeye; Enyew Getaneh Mekonen; Tadesse Tarik Tamir; Berhan Tekeba; Tewodros Getaneh Alemu; Mohammed Seid Ali; Almaz Tefera Gonete; Alemneh Tadesse Kassie; Mulugeta Wassie; Belayneh Shetie Workneh (Maternal Health, Neonatology and Perinatology)
Abstract Background Stillbirth is one of the biggest adverse pregnancy outcomes in countries with low and middle incomes. If current trends continue, 15.9 million babies will be stillborn; nearly half of these (7.7 million, or 48%) will occur in sub-Saharan Africa. Although stillbirth is one of the health care indicators, its prevalence and determinates are not well studied in low- and middle-income countries (LMIC). Therefore, this study aims to assess the prevalence and associated factors of stillbirth among people at extreme ages of reproductive life in Sub-Saharan Africa. Methods Data from the most recent Demographic and Health Surveys, which covered 23 Sub-Saharan African countries from 2015 to 2022, were used for secondary data analysis. The study used a total of 76,451 women. STATA 14 was used to analyze the data. The associated factors of stillbirth were determined using a multilevel mixed-effects logistic retrogression model. Significant factors associated with stillbirth were declared significant at p- value < 0.05. Results The prevalence of stillbirth in Sub-Saharan Africa was 6.18% (95% CI: 6.01, 6.35). Higher odds of stillbirth were observed among women at advanced age (35–49 years) (AOR = 3.72, 95% CI: 2.57, 5.41), those who consumed alcohol during pregnancy (AOR = 1.58, 95% CI: 1.24, 2.00), and those who underwent cesarean section delivery (AOR = 1.23, 95% CI: 1.11, 1.37). Additionally, rural residence (AOR = 1.11, 95% CI: 1.01, 1.23), high community levels of illiteracy (AOR = 1.19, 95% CI: 1.07, 1.32), and residing in South sub-Saharan Africa (AOR = 1.19, 95% CI: 1.03, 1.38) were positively associated with stillbirth. Conclusions This study concludes that stillbirth among women at extreme ages of reproductive life is high compared to the UNICEF 2022 report. The study identified that both individual and community-level variables were associated factors of stillbirth. Therefore, the ministries of health in Sub-Saharan African countries should give attention to those women at the extreme ages of reproductive life and to women from rural areas while designing policies and strategies targeting reducing stillbirth rates.